2014
DOI: 10.1002/ajp.22342
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term fidelity of foraging techniques in common marmosets (Callithrix jacchus)

Abstract: The formation of behavioral traditions has been considered as one of the main building blocks of culture. Numerous studies on social learning in different animal species provide evidence for their capability of successful transmission of information. However, questions concerning the memory and maintenance of this information have received comparably little attention. After the innovation and initial spread of a novel behavior, the behavior should stabilize and be maintained over time. Otherwise, the behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…Exploration–Avoidance and Boldness–Shyness showed a remarkable temporal consistency across 4 years, which supported similar findings of long‐term consistency in personality in other primates (Dutton, 2008; Stevenson‐Hinde et al, 1980a; Weiss et al, 2017), as well as that of the marmosets' consistency in solving extractive foraging tasks across a similar time period (Gunhold et al, 2015). However, we found that a change in breeding status (i.e., from helper to breeder) inside of the family group was linked to the overall increase in the individuals' personality trait Boldness–Shyness (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…Exploration–Avoidance and Boldness–Shyness showed a remarkable temporal consistency across 4 years, which supported similar findings of long‐term consistency in personality in other primates (Dutton, 2008; Stevenson‐Hinde et al, 1980a; Weiss et al, 2017), as well as that of the marmosets' consistency in solving extractive foraging tasks across a similar time period (Gunhold et al, 2015). However, we found that a change in breeding status (i.e., from helper to breeder) inside of the family group was linked to the overall increase in the individuals' personality trait Boldness–Shyness (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…Callitrichids represent the smallest primates, which makes them vulnerable to predation from raptor birds and snakes [Grzimek, ], careful with novel objects and spaces [Fragaszy & Visalberghi, ], and thus, a particularly interesting species for studying the non‐social personality axes. Previous studies noted that individual common marmosets ( Callithrix jacchus ) differ in their reactions to various stimuli, and that this is consistent within an individual, over time [Gunhold et al, ]. Indeed, Koski & Burkart [] have recently found experimental evidence for personality in this species.…”
Section: Introductionmentioning
confidence: 78%
“…There is a wide variety of evidence from demonstrations of imitation in common marmosets ( Bugnyar & Huber, 1997; Voelkl and Huber, 2000), to rapid social learning without reinforcement in cotton-top tamarins (Moscovice & Snowdon, 2006), to long-term retention of socially learned behavior in both marmosets and tamarins in both captivity and the wild (Moscovice & Snowdon, 2006; Gunhold, Massen, Schiel, Souto & Bugnyar, 2014; Gunhold, Range, Huber & Bugnyar, 2015), and of teaching (Humle & Snowdon, 2008, Rapaport, 2011). In addition, wild pygmy marmosets ( Cebuella pygmaea , de la Torre & Snowdon, 2009) have population specific vocal dialects that cannot be explained by habitat acoustics or genetic variation and thus are suggestive of innovations that can spread through a population.…”
Section: Discussionmentioning
confidence: 99%